Yes I am : the Ric Weiland story [videorecording (DVD)] - Quinto, Zachary (Virgil Films, 2023)
Yes, I Am - The Ric Weiland Story chronicles the LGBTQ pioneer & unknown founder of Microsoft. With his newfound wealth, he turned to philanthropy. During his life, he donated more than $200m to fund more than 60 non-profit organizations. His efforts still have a massive impact today. However, as his wealth grew, Ric seemed to slip further into self-doubt, depression, and a kind of impostor syndrome.